Analysis of Changes in Sea Surface Temperature During 2017-2021 at The Coast of Ujung Pangkah Gresik with Landsat 8 Satellite Image Data - Hendrata Wibisana; Zetta Rasullia Kamandang; Kartini (Nusantara Science and Technology Proceedings, 2021)
Changes in sea surface temperature play an important role in climate change that occurs especially in coastal areas such as Ujung Pangkah Gresik. Changes that occur on the coast will affect the lives of people in the area, and these changes will result in anomalies in climate change and other natural phenomena. The purpose of this study is to find changes in Sea Surface Temperature for 5 years to find the right formula for modeling the impact of these changes, which can be overcome in the future. The method developed here is remote sensing technology with Landsat 8 satellite imagery data to extract the digital number value which is converted into a reflectance value to then look for the optimal mathematical model algorithm with parameters of changes in sea surface temperature. The result of this research is that the wavelength of the red channel is the wavelength that can provide the most optimal results compared to the blue channel, the green channel, and the IR channel. From these wavelengths, an exponential mathematical model and a power model are generated which have the best correlation values among several other calculated models. From this study, it can be concluded that Landsat 8 satellite imagery can provide an overview of changes in sea surface temperature on the coast, especially for shallow waters such as Ujung Pangkah Gresik, so that in the future it can be used as an alternative in decision making in coastal management.